Analisis Struktur dan Nilai Moral dalam Lirik Pupuh Album Pupuh Raehan Karya Yus Wiradiredja - Yusup, Andika Maulana; Nuraeni, Leni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated because poetry has the same structure as belief poetry, where belief usually contains moral values. The purpose of this study is to describe the structure and moral values that appear in the butterfly grass. Rumpaka kupuh has a noble value and value about life. This study uses a qualitative approach with a descriptive method. The data analysis technique used in this study is content analysis. The results of the data analysis show that the structure of the song lyrics is in the form of images, symbols or symbols, and musicality or rhythm. There are also other structures that are additional, namely the atmosphere, theme, and language style. Moral values in song lyrics include human morality with his god, human morality with himself, human morality with other humans, human morality with nature, human morality with time, and human morality in the outside and inside